GROWTH AND NODULATION OF MUNGBEAN (VIGNA RADIATA [L.] WILCZEK) AS AFFECTED BY SODIUM CHLORIDE - Elahi, Nosheen N.; Mustafa, Saima; Mirza, Javed I. (Journal of Research (Science), 2004)
The growth and nodulation of Vigna radiata were compared at four levels (0-0.3 % NaCl added to garden soil) of salinity in pot experiments. Dry mass of plants, 7 and 11 weeks after the commencement of salinity treatment, decreased with increasing salinity levels. Number of nodules and fresh weight of nodules per plant decreased with increasing salinity. As the number of nodules decreased, average size of the nodules increased with increasing salinity levels. Reproductive growth was also adversely affected by the salinity as the number and fresh weight of pods per plant decreased with increasing salinity.